2021
DOI: 10.1371/journal.pone.0245362
|View full text |Cite
|
Sign up to set email alerts
|

Germline copy number variations in BRCA1/2 negative families: Role in the molecular etiology of hereditary breast cancer in Tunisia

Abstract: Hereditary breast cancer accounts for 5–10% of all breast cancer cases. So far, known genetic risk factors account for only 50% of the breast cancer genetic component and almost a quarter of hereditary cases are carriers of pathogenic mutations in BRCA1/2 genes. Hence, the genetic basis for a significant fraction of familial cases remains unsolved. This missing heritability may be explained in part by Copy Number Variations (CNVs). We herein aimed to evaluate the contribution of CNVs to hereditary breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…These findings could be explained by the significant variability in GC frequency worldwide as well as risk factors [ 1 ]. Our findings highlight the particular genetic background of the Tunisian population compared to others [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 57%
“…These findings could be explained by the significant variability in GC frequency worldwide as well as risk factors [ 1 ]. Our findings highlight the particular genetic background of the Tunisian population compared to others [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 57%
“…Our results highlight the particular genetic background of the Tunisian population compared to others. Indeed, several papers published in Tunisia have reported the particular genetic background of our population [58][59][60][61].…”
Section: Discussionmentioning
confidence: 97%
“…In neighboring North African region, the frequency of BRCA1/2 pathogenic variants in Moroccan population varied from 16.7 to 31.6% [23]. In Tunisia, 25% of hereditary BC patients carried a BRCA1/2 gene pathogenic variant [24]. The BRCA1/2 variant ratio we found (1:1.18) was also consistent with the fraction reported by these different studies which confirmed the significant contribution of BRCA1/2 germline variant in BC risk among North African populations [25 26].…”
Section: Discussionmentioning
confidence: 99%